Magnetic CuFe2O4 nanoparticles anchored on N-doped carbon for activated peroxymonosulfate removal of oxytetracycline from water: Radical and non-radical pathways - Liu, Xun; Pei, Yan; Cao, Mengbo; Yang, Hongbing; Li, Yongsheng (Chemosphere (Oxford), 2023)
In this work, magnetic CuFe2O4 was prepared for the removal of oxytetracycline (OTC) by a self-propagating combustion synthesis method. Almost complete degradation (99.65%) of OTC was achieved within 25 min at [OTC]0 = 10 mg/L, [PMS]0 = 0.05 mM, CuFe2O4 = 0.1 g/L under pH = 6.8 at 25 °C for deionized water. Specially, the addition CO32− and HCO3− induced the CO3•- appearance enhancing the selective degradation to electron-rich OTC molecule. The prepared CuFe2O4 catalyst exhibited desirable OTC removal rate (87.91%) even in hospital wastewater. The reactive substances were analyzed by free radical quenching experiments and electron paramagnetic resonance (EPR), and the results demonstrated that 1O2 and •OH were the main active substances. Liquid chromatography-mass spectrometry (LC-MS) was used to analyze the intermediates produced during the degradation of OTC and thus to speculate on the possible degradation pathways. Ecotoxicological studies were conducted to unveil large-scale application prospect. [Display omitted] •The self-propagating combustion is facile, effective and time-saving (20 min).•CuFe2O4 have excellent ability to degrade oxytetracycline (99.65%).•The magnetic CuFe2O4 helps to facilitate recycling through magnetism.••OH and 1O2 dominate the degradation process, while SO4•- plays a lower role.